Reaming of Very Precise Holes in Hydrostatic Component - Řehoř, Jan; Fulemová, Jaroslava; Rut, Daniel; Třísková, Veronika; Kutlwašer, Jan; Kouřil, Karel (Manufacturing Technology Journal, 2015)
Nowadays, one of the motive trend in engineering industry is transportation and manipulating technology. The hydrostatic mechanisms belong to the most important components and are created by hydraulic engines, pumps, switchgears etc. Inseparable part of hydraulic engine is a servo-valve which coordinates the fluid flow by a microscopic movement of piston. The servo-valve is a casting, usually made of ductile cast-iron that is necessary to machine. The functionality of hydrostatic circuits is influenced significantly by the precise movement of pistons.Therefore it is necessary to provide the dimension accuracy, machining quality and also the geometric shape of holes. This article describes the issue of holes reaming in hydrostatic components with a use of reamers made of sintered carbide and cermet.
Keywords: hydraulic engine; reaming; sintered carbide; cermet